Neonatology and Paediatric Intensive Care 2017
DOI: 10.1183/1393003.congress-2017.pa2066
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of pulmonary dead space in ventilated newborn infants

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…To our knowledge, the associations of alveolar and anatomical dead space with anthropometric and clinical parameters have not been previously reported using low dead space capnography. We have recently demonstrated that V D‐Phys per kilogram of body weight increases with decreasing weight and gestation, but it is not known whether this relationship is a reflection of lung disease severity or of anthropometric differences in anatomical dead space. The latter is plausible as it has been shown that term‐born newborn infants have higher anatomical dead space per kilogram compared to older children .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, the associations of alveolar and anatomical dead space with anthropometric and clinical parameters have not been previously reported using low dead space capnography. We have recently demonstrated that V D‐Phys per kilogram of body weight increases with decreasing weight and gestation, but it is not known whether this relationship is a reflection of lung disease severity or of anthropometric differences in anatomical dead space. The latter is plausible as it has been shown that term‐born newborn infants have higher anatomical dead space per kilogram compared to older children .…”
Section: Introductionmentioning
confidence: 99%
“…5 Dead space can be calculated using the concentration of carbon dioxide (CO 2 ) in expired breaths measured by capnography. Few studies, however, have used capnography to calculate dead space in ventilated infants 6,7 as it has previously been problematic in prematurely born infants because of technical limitations arising from their high respiratory rates and small tidal volumes and the use of un-cuffed endotracheal tubes (ET) as there may be leakage around such ETs. 8,9 Recently, sensitive, low dead-space CO 2 sensors combined with flow sensors have made the application of real time capnography feasible as a tool to estimate pulmonary dead space at the bedside.…”
mentioning
confidence: 99%
“…It has been demonstrated that infants that remain ventilated develop higher tidal volume requirements despite permissive hypercapnia 7. This likely reflects that infants undergoing prolonged ventilation have an increased dead space 10. Our findings are important as we have identified a volume-targeted level associated with the lowest level of WOB.…”
Section: Discussionmentioning
confidence: 54%
“…Infants born preterm (i.e. <37 weeks’ GA) often have fluid on the lung in addition to greater surface tension within the lungs, higher pulmonary dead space ( V D ) and V D ‐to‐tidal volume ratio, leading to increased collapsibility and decreased area for efficient gas exchange (Dassios, Curley, Morley, & Ross‐Russell, ; Dassios, Kaltsogianni, & Greenough, ; Ghafoor, Mahmud, Ali, & Dogar, ; Helve et al., ; Helve, Janér, Pitkänen, & Andersson, ; Janér et al., ). The most immature infants will have the least developed lung structures.…”
Section: Preterm Physiologymentioning
confidence: 99%